2004
DOI: 10.1002/path.1560
|View full text |Cite
|
Sign up to set email alerts
|

Organ distribution of severe acute respiratory syndrome (SARS) associated coronavirus (SARS‐CoV) in SARS patients: implications for pathogenesis and virus transmission pathways

Abstract: We previously identified the major pathological changes in the respiratory and immune systems of patients who died of severe acute respiratory syndrome (SARS) but gained little information on the organ distribution of SARS-associated coronavirus (SARS-CoV). In the present study, we used a murine monoclonal antibody specific for SARS-CoV nucleoprotein, and probes specific for a SARS-CoV RNA polymerase gene fragment, for immunohistochemistry and in situ hybridization, respectively, to detect SARS-CoV systematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
958
6
50

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,013 publications
(1,046 citation statements)
references
References 25 publications
32
958
6
50
Order By: Relevance
“…5). The principal targets for SARS-CoV infection in humans are the lung and gastrointestinal tract (25,26). SARS-CoV or viral antigens have been detected in type II alveolar cells in lung, and in liver, kidney, sweat glands, parathyroid, brain, pancreas, and adrenal glands (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). The principal targets for SARS-CoV infection in humans are the lung and gastrointestinal tract (25,26). SARS-CoV or viral antigens have been detected in type II alveolar cells in lung, and in liver, kidney, sweat glands, parathyroid, brain, pancreas, and adrenal glands (26).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RT-PCR and immunocytochemistry showed that ACE2 mRNA and protein are expressed on oral, nasal, and intestinal mucosa, alveolar epithelial cells in lung, stomach, skin, lymph nodes, thymus, bone marrow, spleen liver, kidney, and brain, and arterial and venous endothelial cells and arterial smooth muscle cells in many organs (38)(39)(40)(41). These sites for ACE2 expression include most of the sites for SARS-CoV replication in autopsy specimens (26). Our data show that human CD209L can also mediate infection by SARS-CoV, although it is a much less efficient receptor than human ACE2.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,12,25,27 This lesion corresponds in part to the cell types in the respiratory tract in which SARS-CoV antigen has been detected: alveolar epithelial cells (primarily type II pneumocytes), bronchial epithelial cells, and alveolar macrophages. 3,29,33,38,40 Cases of longer duration (more than 10 days) demonstrated features of organizing-phase or late-stage DAD. 7,27 Angiotensin-converting enzyme 2 (ACE2) has been identified as a receptor for the attachment to and uptake of SARS-CoV in host cells.…”
mentioning
confidence: 99%
“…The targets included the lymphocytes, the epithelium of the distal tubules of the kidney, and the submucosal lymphoid complex of the gut, the spleen, and the lymph nodes [7,8]. However, only sporadic information is available regarding the involvement of reproductive organs in SARS patients [9,10]. Because it is known that viruses such as HIV, HBV, and mumps can enter the testis and cause viral orchitis and, in some instances, result in male infertility and testicular tumor [11], we investigated the possible damage of the testis in SARS patients and the effects of SARS on spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%